Entomofauna associated with cowpea Vigna unguiculata (L.) Walp., assessment damages caused by insect pests and predators of Ootheca mutabilis Sahlberg (Coleoptera : Chrysomelidae) in south of Côte d’Ivoire - Landry, Ossey Christian; Nondenot, Aboua Louis Roi; Adagba, Obodji; Christian, Tano Djè Kevin (IJRDO-Journal of Applied Science, 2017)
The necessity to control the insect pests of cowpea (Vigna unguiculata) crops has led to an inventory of insects and assessment of damage caused by pests of this plant. This study was conducted in Adzopé situated in south of Côte d’Ivoire from march to may 2014. Catches were made twice per a week, manually with pliers applying technique of mowing with sweep net and the plants have been inspected to identify damage caused by pests. In total, 44 species have been identified, distributed in 29 families and 9 orders. During the sampling period, 2316 insects were collected. The highest number (927 insects) was recorded at fruiting stage representing 40.03 % of the total catch. Ootheca mutabilis was the most abundant species at the stage before flowering and flowering stage with respectively relative abundances of 39.54 and 30.25 %. Megalurothrips sjostedti was majority at the fruiting stage with a relative abundance of 29.99 %. The analysis of the frequency of occurrence revealed that O. mutabilis was ubiquist species (frequency of occurrence = 100 %) on the crop. Defoliator insects caused the most serious damage at the before flowering stage and flowering stage with respectively attack rates of 78.65 and 96.35 %. At fruiting stage, the highest attack rate (45.83 %) was induced by sucking insects. Among the insects inventoried, three species (Rhinocoris albopilosus, R. rapax and R. bicolor. (Heteroptera : Reduviidae) have been identified as predators of O. mutabilis adults.